RANCANG BANGUN SISTEM INFORMASI POS PELAYANAN TERPADU PADA UPTD PUSKESMAS WATES BERBASIS WEB - Dia Amalia; Mustika Mustika; Arif Hidayat (Universitas Muhammadiyah Metro, 2022)
Technical Management Unit (UPTD) Puskesmas Wates is one of the main health centers in Bumi Ratu Nuban Subdistrict, with a working area covering 10 villages and housing 37 fostered posyandu. Every month the Posyandu carries out monitoring activities for toddlers' growth and development, maternal and child health services such as immunization for disease prevention. The reporting process that occurs at the posyandu is still not computerized and is still done manually by writing each activity into a special book. Lack of knowledge of information technology related to posyandu reporting systems including data on toddlers, data on pregnant women, immunizations, and vitamins. The purpose of this study was to design and build an integrated service post information system at the web-based UPTD Wates Health Center. Using the waterfall method with the PHP programming language and the laravel framework. This information system was built to provide convenience in getting information about posyandu, toddlers, pregnant women, immunizations, vitamins and online activity reports.